Analysis of Consecutive Open Surgeries for Varicose Vein at Dhulikhel Hospital - Karmacharya, RM; Shakya, YR; Shrestha, B (Kathmandu University Medical Journal, 2015)
Background Varicose veins are prominent dilated veins in the lower limb primarily due to disease in the junction between superficial and deep venous system. Operative treatment of such condition significantly improves quality of life and also demonstrably decreases the potential complications. We present with analysis of fifty one consecutive open surgeries for varicose vein at Dhulikhel Hospital.Objective To analyze consecutive open surgeries for varicose vein in terms of gender, age, presenting complaints, findings and post operative outcomes.Method All the cases posted for open surgeries for varicose vein at Dhulikhel Hospital during September 2012 – July 2013 were included. If great saphenous vein in thigh was more than 3 mm, segmental stripping was done. The collected data was analyzed using SPSS version 13.0.Result There were 51 cases with 47%male and 53% female. Mean age was 48.9 years. Prominent dilated vein was the most common presenting complaints. Incompetent saphenofemoral junction was present in 68.6% cases. Segmental stripping was done in 51% cases. Mean days of admission was 2.6 days. Mean pain free day was on 3.2 days. In an average, patient were able to walk normally in 4.1 days. Analysis of hospital admission days, ability to walk normally and pain free day attained in between stripping required and stripping not required group showed significant difference with higher values in stripping required group.Conclusion Although conventional stripping surgery has long been performed for varicose vein, this is associated with prolonged hospital admission, prolonged time required for ability to walk normally, and prolonged time taken for pain free status. Hence newer modalities of treatment like radiofrequency ablation is warranted in our setup too.Kathmandu University Medical Journal Vol.12(3) 2014; 190-193